(untitled) (Al-Farooq Journal of Sciences, 2026)
The study aimed to identify the impact of knowledge management on organizational support in Al-Sahari Bank in Tripoli city. The study adopted knowledge management as the independent variable and organizational support as the dependent variable. A simple random sample of 92 individuals was selected. All 92 questionnaires were analyzed, with no questionnaire excluded, using the SPSS program. The study followed the descriptive-analytical approach to explain the relationship between the variables. The study found that the bank is highly interested in knowledge management and organizational learning. It provides a supportive environment for knowledge generation, sharing, and innovation through cooperation, training, and benefiting from accumulated experiences. The study recommended expanding the use of electronic platforms and organizing periodic meetings to exchange experiences between departments.